1994
DOI: 10.2307/2491389
|View full text |Cite
|
Sign up to set email alerts
|

Analysts' Interim Earnings Forecasts: Evidence on the Forecasting Process

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley and Accounting Research Center, Booth School of Business, University of Chicago are collaborating with JSTOR to digitize, preserve and extend access to Journal of Accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
41
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(65 citation statements)
references
References 23 publications
20
41
2
2
Order By: Relevance
“…This pattern was observed in the whole sample, but also in all three groups separately. We may conclude that our results do not support suggestions about the positive relationship between forecasted horizon and excessive optimism (Kang, O'Brien, & Sivaramakrishnan, 1994;Ramnath, Rock, & Shane, 2008). They do not even support previous empirical findings of Toshino and Suto (2004).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This pattern was observed in the whole sample, but also in all three groups separately. We may conclude that our results do not support suggestions about the positive relationship between forecasted horizon and excessive optimism (Kang, O'Brien, & Sivaramakrishnan, 1994;Ramnath, Rock, & Shane, 2008). They do not even support previous empirical findings of Toshino and Suto (2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Based on our analyses of research studies on this topic to date, it seems that this phenomenon was largely not observed. We found only two other pieces of evidence supporting a positive relation between optimism and forecast horizon in the works of Kang, O'Brien, and Sivaramakrishnan (1994) and Ramnath, Rock, and Shane (2008), although they also lack the theoretical explanation of this phenomenon.…”
Section: Excessive Optimism Of Investment Managers and Financial Analcontrasting
confidence: 69%
See 1 more Smart Citation
“…Previous work related to this issue include psychological surveys as well as empirical studies on professionals' economic forecasts (see, e.g., Fried and Givoly, 1982, O'Brien, 1988, Francis and Philbrick, 1993, Kang et al, 1994, Dreman and Berry, 1995, Giordani and Söderlind, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Fried and Givoly (1982), O'Brien (1988), Francis and Philbrick (1993), Kang, O'Brien, and Sivaramakrishnan (1994), and Dreman and Berry (1995) provide evidence that analysts' forecasts are overly optimistic.…”
Section: Introductionmentioning
confidence: 99%